The Effect of Platelet Number and Haematocrit on Whole Blood Thromboxane Synthesis - Carter, A J; Hanley, S P (Thrombosis and Haemostasis, 1985)
Whole blood, allowed to clot at 37° C in glass tubes, synthesized thromboxane A2 (TxA2) as determined by radioimmunoassay for thromboxane B2 (TxB2). The time course for TxB2 synthesis showed no further increase after 60 min and the concentration of TxB2 in serum obtained from 60 normal subjects positively correlated with the whole blood platelet count in EDTA anticoagulated blood from the same donor.Patients with chronic renal failure produced less serum TxB2 than age- and sex-matched controls; they also had lower haematocrits. After re-calculating TxB2 production as a function of platelet count and haematocrit all but one of the patients fell in the range of values obtained for controls. These results suggest that chronic renal failure may not be associated with a cyclooxygenase defect and that clotted whole blood TxB2 production should be expressed as a function of platelet count and haematocrit.
Keywords: Thromboxane; Platelets; Haematocrit; Chronic renal failure